Impact of the new handling recommendations for hazardous drugs in a hospital pharmacy service - Beatriz G García-Alcántara; Catalina Perelló Alomar; Elena Moreno Centeno; Pilar Modamio; Eduardo L Mariño; Olga Delgado Sánchez Olga Delgado Sánchez Olga Delgado Sánchez (Farmacia Hospitalaria)
Objective: To describe the actions taken by the Pharmacy Unit in a tertiary hospital in order to adapt to the recommendations established by NIOSH 2014 for handling Hazardous Drugs. Method: A retrospective observational study. A list was prepared including all hazardous drugs according to NIOSH 2014 that were available at the hospital as marketed or foreign drugs, or used in clinical trials, and there was a review of the processes of acquisition, repackaging, preparation, circuits, organizational, dispensing and identification. Results: After the analysis, a report including all needs was prepared and sent to the Hospital Management. Any relevant information about the handling and administration of hazardous drugs was included in the prescription computer program. There were changes in the acquisition process of two drugs, in order to avoid splitting and multi-dose formulations. An alternative or improvement was found for 35 253 of the 75 779 units of hazardous drugs repackaged in one year. The Pharmacy Unit took over the preparation of four non-sterile medications, as well as the preparation of all sterile parenteral medications included in Lists 1 and 2 that were not previously prepared there, as well as one from List 3. Information was also included about the preparation processes of Magistral Formulations that involved hazardous drugs from Lists 2 or 3. Conclusion: The adaptation to the recommendations by NIOSH 2014 has represented a change, but also a significant reduction in the handling process of hazardous drugs by the healthcare staff, therefore reducing the risk of occupational exposure.